Transcutaneous Auricular Neurostimulation (tAN): A Novel Adjuvant Treatment in Neonatal Opioid Withdrawal Syndrome - Jenkins, Dorothea D.; Khodaparast, Navid; O’Leary, Georgia H.; Washburn, Stephanie N.; Covalin, Alejandro; Badran, Bashar W. (Frontiers in Human Neuroscience, 2021)
Maternal opioid use during pregnancy is a growing national problem and can lead to newborns developing neonatal opioid withdrawal syndrome (NOWS) soon after birth. Recent data demonstrates that nearly every 15 min a baby is born in the United States suffering from NOWS. The primary treatment for NOWS is opioid replacement therapy, commonly oral morphine, which has neurotoxic effects on the developing brain. There is an urgent need for non-opioid treatments for NOWS. Transcutaneous auricular neurostimulation (tAN), a novel and non-invasive form of electrostimulation, may serve as a promising alternative to morphine. tAN is delivered via a multichannel earpiece electrode worn on and around the left ear, targeting two cranial nerves—the vagus and trigeminal nerves. Prior research suggests that auricular neurostimulation exerts an anxiolytic effect on the body by releasing endogenous opioids and reduces withdrawal symptoms in adults actively withdrawing from opioids. In this first-in-human prospective, open-label trial, we investigated tAN as an adjuvant to morphine therapy in eight infants >33 weeks gestational age suffering from NOWS and receiving oral morphine treatment. Infants received tAN for 30 min 1 h before receiving a morphine dose. tAN was delivered at 0.1 mA below perception intensity at two different nerve targets on the ear: Region 1, the auricular branch of the vagus nerve; and Region 2, the auriculotemporal nerve. tAN was delivered up to four times daily for a maximum of 12 days. The primary outcome measures were safety [heart rate monitoring, Neonatal Infant Pain Scale (NIPS), and skin irritation] and morphine length of treatment (LOT). tAN was well-tolerated and resulted in no unanticipated adverse events. Comparing to the national average of 23 days, the average oral morphine LOT was 13.3 days (median 9 days) and the average LOT after tAN initiation was 7 days (median 6 days). These preliminary data suggest that tAN is safe and may serve as a promising alternative adjuvant for treating NOWS and reducing the amount of time an infant receives oral morphine.